The Role of Augmented Reality (AR) in Enhancing Conceptual Understanding of Geometry in Mathematics Education: Systematic Review - Hassan Muhammad; Nura Ay Musa; Auwal Ahmad; Nurudeen Adamu (Darul Yasin Al Sys, 2026)
Geometry, a fundamental branch of mathematics, often challenges students due to its abstract nature and the demands it places on spatial reasoning and visualization, and traditional teaching methods frequently fail to convey complex geometric concepts effectively, leading to low engagement and poor understanding. This systematic review investigates the impact of Augmented Reality (AR) on enhancing students’ conceptual understanding of geometry in mathematics education by synthesizing existing empirical studies on AR-based geometry instruction. AR technology provides interactive, immersive learning environments that enable learners to manipulate three-dimensional geometric shapes and transformations in real time, thereby supporting deeper cognitive engagement with abstract content. The reviewed studies consistently report that AR interventions enhance spatial reasoning, improve visualization abilities, and foster deeper conceptual understanding of geometric ideas, while also increasing student motivation, engagement, and retention and supporting the development of critical problem-solving skills. At the same time, the review identifies key implementation challenges, including the high cost and limited availability of AR tools, as well as the need for targeted teacher training to design and facilitate AR-enhanced lessons. The review concludes that AR holds strong potential as a pedagogical innovation for geometry education, provided that infrastructural, financial, and professional development barriers are addressed, and recommends future research focusing on longitudinal designs, more affordable AR solutions, and the integration of AR into advanced geometric topics and diverse educational contexts.